2015
DOI: 10.7287/peerj.preprints.1496
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Designing conservation strategies to preserve the genetic diversity of Astragalus edulis Bunge, an endangered species from western Mediterranean region

Abstract: Astragalus edulis (Fabaceae) is an endangered annual species from western Mediterranean region that colonized SE Iberian Peninsula, NE and SW Morocco, and the easternmost Macaronesian islands (Lanzarote and Fuerteventura). Although in Spain some conservation measures have been adopted, it is still necessary to develop an appropriate management plan to preserve genetic diversity across the entire distribution area of the species. Our main objective was to use population genetics as well as ecological and phylog… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Furthermore, we defined rare alleles as those with an overall frequency lower than 10% and existing in less than 40% of the population (Table 2). These were used rather than the pre‐established values (10%–10% or 10%–20%; Peñas et al, 2016; Pérez‐Collazos et al, 2008) due to the relatively low number of rare AFLP alleles obtained with the other values (Caujapé‐Castells & Pedrola‐Monfort, 2004). Regarding the probability of loss of rare bands, we used the equation L = (1 − p ) 2 N (Bengtsson et al, 1995) which considers the band frequency of each rare allele ( p ) and the number of populations in which the rare band is present ( N ) (Pérez‐Collazos et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we defined rare alleles as those with an overall frequency lower than 10% and existing in less than 40% of the population (Table 2). These were used rather than the pre‐established values (10%–10% or 10%–20%; Peñas et al, 2016; Pérez‐Collazos et al, 2008) due to the relatively low number of rare AFLP alleles obtained with the other values (Caujapé‐Castells & Pedrola‐Monfort, 2004). Regarding the probability of loss of rare bands, we used the equation L = (1 − p ) 2 N (Bengtsson et al, 1995) which considers the band frequency of each rare allele ( p ) and the number of populations in which the rare band is present ( N ) (Pérez‐Collazos et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Reports of some studies on genetic diversity of endemic Astragalus species with restricted geographical ranges such as A. sahendii showed that this species has higher genetic diversity than A. tabrizianus, an endemic species with a wider distribution (Nosrati et al, 2015). However, A. edulis exhibits significantly higher genetic diversity in populations that occupy larger areas, have higher numbers of individuals, are stable and are located in protected areas (Penas et al 2016). Genetic variability and the amount of inbreeding depression in A. agnicidus showed that this rare California native species has maintained a certain high level of genetic diversity through an equilibrium between the rate of mutation and the rate of inbreeding (Bencie, 1997).…”
Section: Genetic Diversitymentioning
confidence: 99%
“…This is very important in fragmented populations because they are more vulnerable due to the loss of allelic richness and inbreeding depression (increases homozygosity within populations, Frankham, 2005). Therefore, knowledge of the genetic variability and diversity within and among different populations is crucial for their conservation and management (Cires et al, 2012(Cires et al, , 2013Meloni et al, 2015;Peñas et al, 2016;Esfandani-Bozchaloyi et al, 2018 a, b, c, d). In arid and semi-arid regions, the genus Erodium Aiton (Geraniaceae) includes 74 species and is distributed on all continents, excluding Antarctica (Fiz et al, 2006).…”
Section: Introductionmentioning
confidence: 99%